ANALISIS PENGELOLAAN LEMBAGA PENDIDIKAN LUAR SEKOLAH SENI TARI YAYASAN BI PRODUCTION PEKANBARU - YOCHA LUSSYANA YUSRA; SUMARNO SUMARNO; DUDUNG BURHANUDDIN (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2017)
This research aimed to analyze the planning program of Out-of-SchoolEducational Institution of Dance Art ‘Yayasan BI Production Pekanbaru, the implementationof its program, and its supervision and evaluation. An evaluative method was used in thisresearch putting more emphasis on holistic results of an event being in progress or on-going.The study was carried out on the basis of qualitative approach framework. The findings of theresearch indicated that the planning program of Out-of-School Educational Institution of DanceArt ‘Yayasan BI Production Pekanbaru’ could be said already good which could be seen fromthe program in terms of its objective, policies, strategies and procedures. The organization andthe direction of this foundation cover the structure of organization, function and duties and thedistribution of the teachers’ teaching loads. In terms of supervision and evaluation, this out-ofschooleducational institution is regularly evaluated by the students, teachers and the managerof the foundation. Furthermore, the supervision includes program supervision, self-evaluation,evaluation and curriculum development, accreditation, evaluation of teachers and making efficientuse of educational apparatus.